Nasya Karma: A View Through the Anatomical Exploration of Nasal Epithelium (AYUSHDHARA, 2025)
The nasal route of drug delivery is gaining rapid recognition these days. The modern system of medicine is more concentrating on developing the drugs and methods for the nasal administration. However, this concept has been articulated centuries ago in Ayurveda by the term ‘Nasya karma’. Nasya Karma is a process of administration of medicated oils, ghee, Swarasa or powders into the nasal cavity. Nasya karma is regarded as the most effective treatment in Urdwajatrugata Vikara, as it is quoted ‘Nasa hi shiraso dwaram’ in the context of Nasya. The instilled Nasya dravya reaches the Shringhataka marma and thus reaches the Shira region. In modern anatomy, the components of administered Nasya reach the central nervous system through the neural pathways, vascular routes or by diffusion across nasal mucosa. This dual perspective highlights the potential of Nasya karma, which has a wide range of indications from Urdwajatrugata vikara by the means of local effect to Pumsavana karma as Sarvadaihika benefits. To understand the mode of action and maximize the therapeutic potential of Nasya karma, the comprehensive knowledge of anatomy of nasal epithelium and its physiology is utmost required. This paper explores the possible ways of the action of the drug instilled through nasal pathway is explained.